ANALISIS PENGARUH LATIHAN FOOTWORK TERHADAP KECEPATAN REAKSI DAN AKURASI PUKULAN FOREHAND PADA ATLET TENIS LAPANGAN JUNIOR - Rafli Rama Randau; Anggraeni, Emayanti; Mukharrar Fadjri; Ahmad Wael (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of footwork training on reaction speed and forehand accuracy in junior tennis players. The research involved 30 junior athletes who were measured before (pretest) and after (posttest) undergoing a structured footwork training program. Data collection methods included reaction speed tests using visual stimuli and forehand accuracy measurements through target zones on the court. Data were analyzed using a paired sample t-test to determine the significance of differences between pretest and posttest results. The results showed that footwork training significantly affected reaction speed, with the average reaction time decreasing from 0.53 seconds to 0.46 seconds (mean difference = 0.07 seconds; t = 6.12; p = 0.000), and forehand accuracy, with the average score increasing from 63.20 to 75.40 points (mean difference = 12.20 points; t = 8.45; p =0.000). These findings indicate that footwork training effectively enhances athletes’ ability to respond quickly to stimuli and perform more accurate forehand strokes. Practically, junior tennis coaches are recommended to integrate footwork training regularly into training programs to improve technical performance and match readiness